PENGARUH NPK TERHADAP PERTUMBUHAN BAYAM HIJAU (Amaranthus Tricolor) - Mahrus Ali; nurlina; Yeni Ika Pratiwi (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
The study was to determine the effect of NPK fertilizer on plant growth green amaranth (Amaranthus tricolor) Research conducted at the Faculty of Agriculture Experimental garden University Merdeka Surabaya. Research is a factorial experiment were prepared using the method of randomized block design (RAK), consisting of 1 factorial and 3 repetitions. each treatment in the first repeat consists of 2 samples or plant samples. One factor that green spinach plants: P0 green spinach without NPK / polybag, green Spinach P1 at a dose of NPK fertilizer 0.9 gram/polybag, P2 green Spinach at a dose of NPK fertilizer 1.8 gram/polybag, P3 green Spinach at a dose of fertilizer NPK 2.7 gram/polybag, P4 green Spinach at a dose of NPK fertilizer 3.6 gram/polybag, P5 green Spinach at a dose of NPK fertilizer 4.5 gram/polybag, P6 green Spinach at a dose of NPK fertilizer 5.4 gram/polybag. The results showed that treatment of NPK fertilizer on plant growth green spinach shows the real effect on plant height, leaf number, fresh weight per polybag, per plant fresh weight, dry weight per plant. The best results are obtained wet weight per polybag on NPK fertilizer treatment P3 (green spinach at a dose of NPK fertilizer 2.7 gram/polybag) which is 223.41 grams.